Brain ischemia downregulates the neuroprotective GDNF-Ret signaling by a calpain-dependent mechanism in cultured hippocampal neurons - Curcio, M. (2015)
The glial cell line-derived neurotrophic factor (GDNF) has an important role in neuronal survival through binding to the GFRα1 (GDNF family receptor alpha-1) receptor and activation of the receptor tyrosine kinase Ret. Transient brain ischemia alters the expression of the GDNF signaling machinery but whether the GDNF receptor proteins are also affected, and the functional consequences, have not been investigated. We found that excitotoxic stimulation of cultured hippocampal neurons leads to a calpain-dependent downregulation of the long isoform of Ret (Ret51), but no changes were observed for Ret9 or GFRα1 under the same conditions. Cleavage of Ret51 by calpains was selectively mediated by activation of the extrasynaptic pool of N-methyl-d-aspartate receptors and leads to the formation of a stable cleavage product. Calpain-mediated cleavage of Ret51 was also observed in hippocampal neurons subjected to transient oxygen and glucose deprivation (OGD), a model of global brain ischemia, as well as in the ischemic region in the cerebral cortex of mice exposed to transient middle cerebral artery occlusion. Although the reduction of Ret51 protein levels decreased the total GDNF-induced receptor activity (as determined by assessing total phospho-Ret51 protein levels) and their downstream signaling activity, the remaining receptors still showed an increase in phosphorylation after incubation of hippocampal neurons with GDNF. Furthermore, GDNF protected hippocampal neurons when present before, during or after OGD, and the effects under the latter conditions were more significant in neurons transfected with human Ret51. These results indicate that the loss of Ret51 in brain ischemia partially impairs the neuroprotective effects of GDNF.